The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acsami.5b05851
|View full text |Cite
|
Sign up to set email alerts
|

Application Of Phenol/Amine Copolymerized Film Modified Magnesium Alloys: Anticorrosion And Surface Biofunctionalization

Abstract: Magnesium metal as degradable metallic material is one of the most researched areas, but its rapid degradation rate restricts its development. The current anticorrosion surface modification methods require expensive equipment and complicated operation processes and cannot continue to introduce biofunction on modified surface. In this study, the GAHD conversion coatings were fabricated on the surface of magnesium alloys (MZM) by incubating in the mixture solution of gallic acid (GA) and hexamethylenediamine (HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 39 publications
(80 reference statements)
2
37
0
Order By: Relevance
“…According to the corrosion reaction of Mg + H 2 O → Mg 2+ + OH − + H 2 (gas), both the hydrogen evolution and the change of pH value can reflect the corrosion rate of the sample 32 , 33 . Figure 6b and c exhibit the hydrogen evolution and the corrosion rate of all samples.…”
Section: Resultsmentioning
confidence: 99%
“…According to the corrosion reaction of Mg + H 2 O → Mg 2+ + OH − + H 2 (gas), both the hydrogen evolution and the change of pH value can reflect the corrosion rate of the sample 32 , 33 . Figure 6b and c exhibit the hydrogen evolution and the corrosion rate of all samples.…”
Section: Resultsmentioning
confidence: 99%
“…According to the published data of XPS spectra for C 1s of MAO and MAO-GA, 284.7 eV and 285.9 eV were attributed to aliphatic C and C–O, respectively ( Figure 4 a) [ 26 ]. In addition, 288.6 eV was ascribed to COOH, COOR, COO − and C=O (quinonyl) [ 27 ]. The area ratio of the carboxyl related group for the MAO-GA group, which is the characteristic of GA, was around 22%, proving that GA immobilizes on the MAO coating after the sample is immersed for 24 h. For O 1s, 530.9 eV belongs to aromatic C=O and magnesium oxide, while 531.7 eV is ascribed to O=C–OH and magnesium hydroxide ( Figure 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…The area ratio of the carboxyl related group for the MAO-GA group, which is the characteristic of GA, was around 22%, proving that GA immobilizes on the MAO coating after the sample is immersed for 24 h. For O 1s, 530.9 eV belongs to aromatic C=O and magnesium oxide, while 531.7 eV is ascribed to O=C–OH and magnesium hydroxide ( Figure 4 b). Moreover, the peaks of magnesium silicate and O=C–O − (magnesium carboxylate) are very close, which are 532.8 eV and 532.4 eV, respectively; 533.5 eV is assigned to the hydroxyl group and carboxyl group, and the targeted oxygen is different from the 531.7 eV peak of GA [ 27 ]. In the oxygen spectra of the MAO group, the data showed that the coating consisted mostly of magnesium oxide and magnesium silicate, which was agrees well with the EDX and XRD data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations